Design and development of a climatic wind tunnel for physiological sports experimentation. (March 2019) - Ainegren, Mats; Tuplin, Simon; Carlsson, Peter; Render, Peter
The aim of this project was to develop a wind tunnel that enables the study of human performance during various types of sports and physical activities by examining the influence of aerodynamic drag, precipitation, frictional forces and gravitational forces on uphill and downhill travel on a moving substrate. An overall design for a wind tunnel and working section containing a large treadmill was drafted, followed by computational fluid dynamics simulations of flow conditions to assess the design's feasibility and select from different geometries prior to its construction. The flow conditions in the completed wind tunnel were validated using different flows, speeds and treadmill inclinations. Pilot experiments were carried out using a cross-country skier to investigate the effect of aerodynamic drag on oxygen uptake during double poling and the maximal achieved speed when rolling on a declined treadmill. The purpose was to validate the usefulness of the tunnel. The results showed that flow conditions are acceptable for experiments even in worst-case scenarios with maximal inclined and declined treadmill. Results also showed that aerodynamic drag has a significant impact on the skier's energy expenditure.